Diabetes mellitus in pheochromocytoma and paraganglioma: Prevalence, dynamics of insulin secretion / sensitivity and predictors of remission. Issue 6 (November 2020) - Khatiwada, Saurav; Agarwal, Shipra; Kandasamy, Devasenathipathy; Jyotsna, V.P.; Kumar, Rajeev; Kumar Bansal, Virinder; Pandey, R.M.; Gupta, Nandita; Tandon, Nikhil
Abstract: Background and aims: Pheochromocytoma and paraganglioma (PPGL) are associated with dysglycemia and diabetes mellitus (DM) much of which improves post operatively. In this study, we set out to ascertain pre and post-operative prevalence of DM in patients with PPGL based on oral glucose tolerance test (OGTT) and HbA1c and to evaluate effect of insulin secretion and sensitivity indices on DM pre-operatively. Methods: Clinical and anthropometric data collection, HbA1c, 75 g OGTT with serum insulin estimation were done pre-operatively (n = 34) and at follow-up after successful surgery (n = 24) in patients with PPGL. Results: Pre and post-operative prevalence of DM were 48%(18/37) and 17% (4/24) respectively. Comparison of patients with highest (Q4) and lowest (Q1) quartiles of insulinogenic index (IGI), a parameter of insulin secretion, revealed trends towards higher prevalence of DM in patients with lower IGI (Q4 to Q1: 29% versus 71%, n = 28, p = 0.24)but no association was observed with HOMA-IR (Q4 to Q1:50% versus 57%, n = 28, p = 1.00), an insulin sensitivity index. DM remitted in 77% patients post-operatively, predicted by duration of DM of<3 years. Conclusion: There is high prevalence of DM in PPGL, with marked remission post-operatively, especially predicted by shorter duration of DM. Impaired insulin secretion is more strongly associated with pre-operative DM than increased insulin resistance. Highlights: Pheochromocytoma and Paraganglioma cause a reversible form of diabetes mellitus. Pre-operative prevalence of diabetes was 48%, which decreased to 17% post operatively. Duration of diabetes less than three years and lower HbA1c were significantly associated with remission. Impaired insulin secretion, rather than impaired insulin sensitivity, was predominant factor.